THE PHYSIOCHEMICAL AND ANTIBACTERIAL PROPERTIES OF GALACTOMANNAN EDIBLE FILM OF ARENGA PINNATA INCORPORATED WITH ZINGIBER OFFICINALE ESSENTIAL OIL - Br Tarigan, Juliati; Nainggolan, Irwana; Kaban, Jamaran (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to demonstrate the incorporation of Zingiber officinale essential (ZOE) oil onto galactomannan from Arenga pinnata (GAP) matrix and determined the antibacterial activity of the edible films (EF). Methods: EF was obtained from the incorporation of GAP (0.5, 0.9, or 1.3 g) with ZOE (0.5 or 1 g) using glycerol (0.6 g) and monoglycerol oleic (0.2 g) as a plasticizer. Results: The thickness of the films increased with the increase of GAP and ZOE oil. However, the tensile strength and water permeability decreased in the fourth EF when the ZOE oil was increased. The maximum value of tensile strength and modulus elongation was obtained with the ratio of GAP to ZOE oil at 0.9, 0.5, 4.502 MPa, and 0.0633 MPa, respectively. The Fourier transform infrared spectrum showed that the interaction occurred between GAP and ZOE oil. The EFs showed antibacterial activity against Escherichia coli, Staphylococcus aureus, Shigella dysenteriae, Salmonella typhi, Pseudomonas aeruginosa, Candida albicans, and Saccharomyces cerevisiae with the highest activity in the third EF. The total bacteria amount in a colony decreased until the 5th day compared with the control. Furthermore, the third EF could inhibit oxygen migration with a respiratory quotient of 7.71. Conclusions: This study revealed that EFs from GAP and ZOE could be prepared and have antibacterial activity against several pathogenic bacteria. Â